Effects of Clostridium difficile toxin A on K562/A02 cell proliferation, apoptosis and multi-drug resistance - Xi, Yaming (Oncol Lett, 2018)
The aim of the present study was to investigate the cytotoxic effect and multi-drug resistance (MDR) of Clostridium difficile toxin A (TcdA) on K562/A02 cells, and understand its underlying molecular pathways. K562/A02 cells were treated with TcdA at different concentrations for 24, 48 and 72 h, and the inhibition effect and drug resistance of TcdA on K562/A02 cell proliferation was assessed by methyl thiazolyl tetrazolium colorimetric assay. Furthermore, cell cycle-apoptosis was analyzed by flow cytometry, P-glycoprotein (P-gp) expression was determined by western blot analysis and caspase-3 activity was measured using a caspase-3 activity kit. TcdA inhibited K562/A02 cell proliferation in a time- and dose-dependent manner. The inhibition rate of K562/A02 cells reached 8.76±0.76, 28.55±0.43, 47.89±0.27, 58.08±0.06 and 57.70±0.79% following treatment with 50, 100, 200, 400 and 800 ng/ml TcdA, respectively, for 24 h. K562/A02 cells in the G0/G1 phase increased and cells in the S phase decreased following treatment with TcdA (P<0.05), and the apoptotic rates in the 200 and 400 ng/ml concentration groups were 14.05 and 22.89%, respectively. In addition, TcdA (50 ng/ml) significantly inhibited the proliferation of K562/A02 cells and reduced the half maximal inhibitory concentration of these drugs in combination with chemotherapy drugs. The reversal folds were 3.09, 2.89 and 2.79, respectively. Furthermore, TcdA treatment was associated with the upregulation of P-gp in K562/A02 cells, and caspase-3 activity was observed to increase in K562/A02 cells following TcdA treatment, when compared with untreated controls (P<0.05). These findings suggested that TcdA may be able to inhibit K562/A02 cell growth, induce cell apoptosis by decreasing P-gp levels and caspase-3 activation, and partially reverse MDR. Further studies are required to evaluate the potential of TcdA as a candidate for the chemotherapy of hematologic malignancies.